Effect of compressive force combined with vibration on CCL2 and CCL5 in human periodontal ligament cells - Supunsa Pongtiwattanakul; Chidchanok Leethanakul; Onnicha Rattanaporn; Peungchaleoy Thammanichanon; Sissada Tannukit (Elsevier, 2024)
Purpose: To investigate the effect of compressive force combined with vibration on expression of CC-chemokine ligand 2 (CCL2) and 5 (CCL5) in human periodontal ligament (hPDL) cells. Methods: Human PDL cells were cultured and assigned into four groups: control (Con), compressive force 2.0 g/cm2 for 24 h and 48 h (C), vibration 0.3 g 30 Hz for 20 min every 24 h (V), and compressive force combined with vibration (VC). At 24 h and 48 h, mRNA and protein levels of CCL2 and CCL5 were examined by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assay (ELISA), respectively. Results: At 24 h and 48 h, CCL2 mRNA and protein levels in C and VC were significantly higher than Con. At 24 h, VC showed significantly higher CCL2 mRNA expression than C. However, there was no significant difference between CCL2 protein in C and VC at both time points. At 24 h and 48 h, CCL5 mRNA expression was significantly down-regulated in V and VC, whereas CCL5 protein was undetectable in all groups. Conclusions: Application of compressive force combined with vibration resulted in the upregulation of CCL2 mRNA and protein levels, whereas CCL5 mRNA expression was down-regulated.